Creation of new anastomosis for management of obstructive symptoms related to gastrojejunal anastomosis in patients who undergo gastric bypass: a case series - Rohit Agrawal, MD; Ethan M. Cohen, MD; Ayowumi A. Adekolu, MD; Soban Maan, MD; Mouaz Haffar, MD; Monica Chowdhry, MD; Shyam Thakkar, MD; Shailendra Singh, MD (VideoGIE)
Background and Aims: Roux-en-Y gastric bypass (RYGB) is associated with gastrojejunal (GJ) strictures in up to 20% of patients. Surgical revision of the GJ anastomosis is technically challenging and carries significant morbidity, making endoscopic therapies such as endoscopic balloon dilation (EBD) and stent placement the preferred approach. In addition, the angulation of GJ anastomosis relative to the Roux limb can cause obstructive symptoms, which are less amenable to EBD or stent placement. In patients with refractory strictures and/or angulation, we evaluate the safety and feasibility of a new anastomosis EUS-guided gastroenterostomy as an alternative to surgical revision. Methods: In patients with refractory GJ strictures and/or angulation, a new anastomosis EUS-guided gastroenterostomy between the gastric pouch and Roux limb is created. Results: Our case series includes 6 patients with a history of RYGB referred for management of obstructive symptoms. Upper endoscopy revealed severe GJ stenosis in 2 patients, complete obliteration of GJ anastomosis in 1 patient, stenosis with angulation in 1 patient, and angulation only in 2 patients. Four patients underwent previous unsuccessful attempts at balloon dilation. Lumen-apposing metal stent (LAMS) placement was initially performed in 4 patients, resulting in resolution of symptoms. However, their symptoms recurred after LAMS removal. EUS-guided anastomosis between the gastric pouch and Roux limb was created successfully in all patients, with no major adverse events. One patient experienced LAMS migration after 54 days. Patients had complete resolution of symptoms after the new anastomosis anastomosis was created. Conclusions: Our case series highlights the safety and feasibility of EUS-guided gastroenterostomy as an alternative to surgical revision in such patients. Large prospective studies with longer follow-up are needed to assess long-term outcomes of this intervention.